The abundance diversity of insect pollinator in star fruit - Abdullah Radzy, Emir Naqib (2017)
Star fruit is one of the main fruit that been produce by Malaysia in large scale. The higher production of star fruit shows that it has a highly demand worldwide. Star fruit is the type of crop that need cross pollination in order to produce fruit set. Thus, the cross pollination process is widely been carried by insect. However the declining number of insect pollinator due to many factor such as climate change, urban agriculture and disease caused declining number of insect pollinator. The declining number of insect pollinator told us that we need to manage the existence species of insect pollinator before extinction happen. This experiment was conducted to identify the abundance number of insect pollinator in star fruit. The result of this experiment will help farmer and grower to manage their insect pollinator in sustainable way. All of the insect that visit the flower of the selected tree will be collected as sample. The experiment was conducted in two ways which is sampling and observation of the insect. The collected insect was been determine by referring to collection insect in museum of entomology, Department of Plant Protection, Faculty of Agriculture UPM. The data collected showed that there are four order of insect that visit the star fruit flower which is Hymenoptera, Diptera, Lepidoptera and Coleoptera. Based on the result obtained, there are 15 species of insect that visit the star fruit flower and the main species is Genotrigona thoracica. This proved that G. thorracica is the most abundance insect pollinator in star fruit compared to other species of insect that been collected.